Random epigenetic modulation of CHO cells by repeated knockdown of DNA methyltransferases increases population diversity and enables sorting of cells with higher production capacities. Issue 11 (24th July 2020) - Weinguny, Marcus; Eisenhut, Peter; Klanert, Gerald; Virgolini, Nikolaus; Marx, Nicolas; Jonsson, Andreas; Ivansson, Daniel; Lövgren, Ann; Borth, Nicole
Abstract: Chinese hamster ovary (CHO) cells produce a large share of today's biopharmaceuticals. Still, the generation of satisfactory producer cell lines is a tedious undertaking. Recently, it was found that CHO cells, when exposed to new environmental conditions, modify their epigenome, suggesting that cells adapt their gene expression pattern to handle new challenges. The major aim of the present study was to employ artificially induced, random changes in the DNA‐methylation pattern of CHO cells to diversify cell populations and consequently increase the finding of cell lines with improved cellular characteristics. To achieve this, DNA methyltransferases and/or the ten‐eleven translocation enzymes were downregulated by RNA interference over a time span of ∼16 days. Methylation analysis of the resulting cell pools revealed that the knockdown of DNA methyltransferases was highly effective in randomly demethylating the genome. The same approach, when applied to stable CHO producer cells resulted in (a) an increased productivity diversity in the cell population, and (b) a higher number of outliers within the population, which resulted in higher specific productivity and titer in the sorted cells. These findings suggest that epigenetics play a previously underestimated, but actually important role in defining the overall cellular behavior of production clones. Abstract : Weinguny and coworkers demonstrate that overall DNA methylation patterns in Chinese hamster ovary (CHO) cells can effectively be randomized by a knock‐down of DNA methyltransferases (DNMT) using small interfering (si)RNAs. These DNA methylation changes increase the phenotypic diversity in a CHO cell population producing a recombinant protein. This newly generated diversity eventually facilitated the isolation of cells with increased production capacities and highlights the importance of epigenetic regulation and its impact on the phenotype of mammalian cell factories.